The Impact of Attenuated Porcine Reproductive and Respiratory Syndrome (PRRS) Vaccine on the Efficacy of Subunit Classical Swine Fever Vaccine - R. Madera; L. Wang; A. G. Cino-Ozuna; J. Shi (Kansas Agricultural Experiment Station Research Reports, 2020)
Commercial pigs have been routinely injected with multiple vaccines that are either administered separately or co-administered at the same time for convenience, and to minimize pig stress. However, viruses, including attenuated and modified live virus (MLV) vaccines, can modulate host immune responses that could potentially impact the efficacy of co-administered vaccines. Here we report the effects of pre- and co-administered Chinese highly pathogenic porcine reproductive and respiratory syndrome (PRRS) virus MLV, JXA1-R, on the efficacy of an emulsion-based classical swine fever virus (CSFV) subunit vaccine, KNB-E2. Immune responses to the CSFV and JXA1-R vaccines were evaluated by testing CSFV-specific and PRRSV-specific sera antibodies and then challenged with CSFV at 4 weeks post KNB-E2 vaccination. Pigs co-administered with JXA1-R vaccine and pigs vaccinated with JXA1-R two weeks before KNB-E2 vaccination had slightly lower CSFV-specific antibodies than pigs vaccinated with KNB-E2 alone at 3 weeks post KNB-E2 vaccination. However, both groups of JXA1-R/KNB-E2 vaccinated pigs were amply protected from CSF clinical symptoms upon challenge. The immunological responses affected by various multiple vaccination combinations in swine would be an interesting aspect for future investigations.
Keywords: PRRS; CSF; classical swine fever; subunit vaccine; KNB-E2